ANALISIS HARGA SAHAM PERUSAHAAN JAKARTA ISLAMIC INDEX YANG TERDAFTAR DI BEI TAHUN 2018-2022 - Putriyani, Leni; Setiyanti, Sri Wiranti; widyartati, penta (Sekolah Tinggi Ilmu Ekonomi Semarang, 2024)
In the era of globalization and free markets, there is a lot of intense competition between business actors to maintain the continuity of their companies by increasing capital in the form of debt or issuing shares. Looking at market capitalization growth where there are ups and downs in stock prices that are influenced by several factors, one of which is financial ratios. The purpose of this study is to determine the Effect of Current Ratio, Return on Asset and Debt to Equity Ratio on the Share Price of Jakarta Islamic Index Companies listed on the IDX for the 2018-2022 period. The population in this study is 30 companies included in the Jakarta Islamic Index group listed on the Indonesia stock exchange for the 2018-2022 period. The sampling method in this study uses purposive sampling and ampelous that meets the criteria in this study are 15 (fifteen) companies. The variables used in this study are Current Ratio (X 1), Return on Assets (X 2), Debt to Equity Ratio (X3) and Stock Price (Y). The data used in this study are secondary data from www.idx.co.id and www.finance.yahoo.com. The analytical method in this study uses quantitative descriptive and hypothesis testing using multiple linear regression analysis methods with SPSS 24 tools. The results showed that the Current Ratio (X 1) did not have a significant effect on the stock price with a significant value of 0.777 > 0.05, Return on Asset (X 2) had a significant effect on the stock price with a significant value of 0.008 < 0.05, and the Debt to Equity Ratio (X3) did not have a significant effect on the stock price with a significant value of 0.383 > 0.05. The advice in this study is for potential investors who want to invest their funds must pay attention to and weigh Return on Assets because in this study it is proven to affect the share price of companies listed on the Jakarta Islamic Index on the IDX for the 2018-2022 period, besides that investors must also pay attention to other financial performance and must pay attention to company performance and The overall economic condition of the company that can have an impact on capital market conditions. For further researchers, it is recommended to increase financial ratios, increase the number of populations or samples and increase the period of more extended research so that it is expected to provide better research results and can expand research.